Pengetahuan Siswa Tentang Bantuan Hidup Dasar (BHD) Dengan Motivasi Menolong Korban Henti Jantung Pada Pelajar SMA - Syaiful Syaiful; Dahlan Dahlan; Rachel Larasati; Martiningsih Martiningsih (Poltekkes Kemenkes Mataram, 2019)
Basic life support is emergency action for free your breath, help breathing and maintaining blood circulation without using aids. Basic life support knowledge (BLS) is knowledge and skills. Knowing the theory itself without practice makes motivation to be helpful and mentally untrained when actually dealing with real events. The aims of this study was to know the relation student knowledge of basic life support (BLS) with the motivation of helping victims of cardiac arrest at senior high school 02 in bima city on 2019. Design was used in this research was corelational. with cross sectional design. Sampling techniques using cluster sampling with 38 sample respondents. The research instrument used was a questionnaire. data analyzed using spearman rank test with significant level (α = 0.05). The results showed that students’ knowledge of BLS was mostly good with a percentage of 63,8 % and motivation to help victims of cardiac arrest was mostly high a percentage of 60,5 %. The results of data were analyzed by correlation test using spearman rank obtained a value of p = value α = 0,05. Because the value of p = 0.000 <value α = 0.05, then means that H0is rejected and Ha is accepted. There is a relationship between students' knowledge about basic life assistance (BLS) and the motivation to help victims of cardiac arrest at SMAN 02 Kota Bima.